Nuclear medicine and PET/​CT : (Elsevier, 2012)
Nuclear Medicine and PET/CT: Technology and Techniques provides a single source for state-of-the-art information on all aspects of nuclear medicine. Coverage includes relevant anatomy and physiology and discusses each procedure in relation to the specific use of radiopharmaceuticals and the instruments required. Edited by experts in nuclear imaging and PET/CT, Paul E. Christian and Kristen M. Waterstram-Rich, this edition has a new chapter on MRI as it relates to nuclear medicine and includes practical, step-by-step instructions for procedures.